Interventions éducatives pour la prévention des deficits énergétiques relatifs dans le sport (REDs) : une revue exploratoire - Chantler, J.; MacMillan, C.; Sewry, N. (Science & Sports, 2026)
Background and objectives Athletes, coaches, and support staff generally lack adequate knowledge of Relative Energy Deficiency in Sport (REDs) and its causes, and one way to address this is through the use of educational interventions (EI). This scoping review aimed to summarise existing literature and identify research gaps concerning EI's for REDs and its physiological effects on athletes.